RELATIONSHIP BETWEEN THE INSERTION/DELETION VARIANTS OF POU1F1, FSHΒ, ANDMUC13 AND TESTIS MEASUREMENT TRAITS IN MALE PIGLETS - Fa Ren; Shuai Yu; Xuelian Zhang; Xiaoyan Lv; Xiuzhu Sun1 andChuanying Pan1 (Journal of Animal and Plant Sciences, 2017)
The aim of this study was to investigate the insertion/deletion (indel) mutations of the POU domain class 1 transcription factor 1 (POU1F1), the follicle-stimulating hormone β-subunit (FSHβ), and themucin 13 (MUC13) genes, as well as to evaluate their associations with testis measurement traits in male piglets. In total, these indels were analyzed in 442 individuals from two pig breeds by PCR and agarose gel electrophoresis. As a result, three genotypes (homozygous insertion and heterozygote and homozygous deletion) were found at each locus. Association analyses revealed a significant relationship between POU1F1 indel and testis short girth (TSG) in 15-day-old Large White (LW) pigs (P = 0.016). At the POU1F1indel locus, the testis measurement traits of pigs with the AA and AB genotypes were larger than those of pigs with the BB genotype. As for FSHβ, an indel was found to be significantly associated with testis long circumference (TLC) (P = 0.050) and testis weight (TW) (P = 0.001) of 40-day-old Landrace (LD) piglets, with the BB genotype showing the largest testis measurement traits. We found no significant relationships between indels of MUC13 and the testis measurement traits. The significant influence of indels ofPOU1F1 and FSHβ suggests that both POU1F1 and FSHβ influence reproductive potential, and therefore, could be possible candidate genes for the breeding improvement of male piglets.
Keywords: Pigs; POU1F1 gene; MUC13 gene; FSHβ gene; Insertion/deletion (indel)